UJI KEEFEKTIFAN BIOKOMPOS âTRICHOSUBUR PROTECTâ TERHADAP PERTUMBUHANTANAMAN BAWANG MERAH (ALLIUM ASCALONICUML.) - Rahmania, Rahmania; Umrah, Umrah; Thaha, Abdul Rahim (AGROTEKBIS, 2017)
"Trichosubur Protect", are biocompost form of ranule preparation, an active agent of Trichoderma sp, with the ingredients are Nitrogen (2.39%), Posfor (0.14%), Potassium (0.90%), Calcium (0.02%), Sodium (0.27%), Sulfur (0.53%) and C-organic (51.13%), this Product from Biology Department, Mathematics and Natural Sciences Faculty of Tadulako University. This research aimed to the test effectiveness and the dosage biocompost "Trichosubur Protect" effect on the growth of the onion plants (Allium ascalonicumL.).This research was conducted at November 2015 until March 2016, located at hotusbotanicus in Tadulako University. This research was designed in a Completely Randomized Design, consisting of six treatment and three times replications. With these following treatment arrange; P0 (without given biocompost "Trichosubur Protect"), P1 (10g biocompost "Trichosubur Protect"), P2 (20g), P3 (30g), P4 (40g) and P5 (2g NPK fertilizer). The research showed that P4 treatment the best onion plants growth comparative with the P0, P1, P2 and P3 treatment. P4 treatment showed the number of tubers was 7.66, biomass weight at harvest 4.43g, leaf weight at harvest 4.25g tuber, weight at harvest 15.12g, hand root weight at harvest 0.13g, nevertheless it is lower than P5 treatment. Keywords : Biocompost "Trichosubur Protect", Onion (Allium ascalonicumL.), Trichoderma sp..